Interplay Between Oxytetracycline and the Homozygote kdr (L1014F) Resistance Genotype on Fecundity in Anopheles gambiae (Diptera: Culicidae) Mosquitoes. Issue 4 (11th August 2021) - Medjigbodo, Adandé A; Sonounameto, Eric G; Djihinto, Oswald Y; Abbey, Emmanuella; Salavi, Esther B; Djossou, Laurette; Badolo, Athanase; Djogbénou, Luc S
Abstract: The insecticide resistance in Anopheles gambiae mosquitoes has remained the major threat for vector control programs but the fitness effects conferred by these mechanisms are poorly understood. To fill this knowledge gap, the present study aimed at testing the hypothesis that antibiotic oxytetracycline could have an interaction with insecticide resistance genotypes and consequently inhibit the fecundity in An. gambiae . Four strains of An. gambiae : Kisumu (susceptible), KisKdr ( kdr (L1014F) resistant), AcerKis ( ace-1 (G119S) resistant) and AcerKdrKis (both kdr (L1014F) and ace-1 (G119S) resistant) were used in this study. The different strains were allowed to bloodfeed on a rabbit previously treated with antibiotic oxytetracycline at a concentration of 39·10 –5 M. Three days later, ovarian follicles were dissected from individual mosquito ovaries into physiological saline solution (0.9% NaCl) under a stereomicroscope and the eggs were counted. Fecundity was substantially lower in oxytetracycline-exposed KisKdr females when compared to that of the untreated individuals and oxytetracycline-exposed Kisumu females. The exposed AcerKis females displayed an increased fecundity compared to their nontreated counterparts whereas they had reduced fecundity compared to that of oxytetracycline-exposed Kisumu females. There was no substantial difference between the fecundity in the treated and untreated AcerKdrKis females. The oxytetracycline-exposed AcerKdrKis mosquitoes had an increased fecundity compared to that of the exposed Kisumu females. Our data indicate an indirect effect of oxytetracycline in reducing fecundity of An. gambiae mosquitoes carrying kdr R (L1014F) genotype. These findings could be useful for designing new integrated approaches for malaria vector control in endemic countries.